"Host-Guest" crystalline Mo/Co-framework induced phase-conversion of MoCx in carbon hybrids for regulating absorption of electromagnetic wave. (September 2022) - Huang, Wenhuan; Chen, Jiamin; Gao, Wenming; Wang, Lei; Liu, Panbo; Zhang, Yanan; Yin, Zheng; Yang, Yuhao
Abstract: Unveiling the structural design and synthesizing mechanism of the metallic crystalline precursors is of great significance for constructing hetero-interfaces and enhancing the EW attenuation in electromagnetic wave absorbing materials (EWAMs). Herein, two diverse crystalline Mo-species incorporated metal-organic framework precursors were designed for studying the phase conversion during the high-temperature treatment and evaluating their electromagnetic wave (EW) absorbing mechanism. The MoO4 as the node on the framework and the Mo12 O40 cluster as guest in the framework derived β -Mo2 C and η -MoC in MoCx /Co@NC hybrids, respectively. The EW absorbing performance results indicated a superior RL min of −47.72 dB at 11.76 GHz at the thickness of 2.0 mm and a wide effective absorption bandwidth (EAB) of 4.58 GHz (7.44–12.02 GHz) covering the whole X-band at the thickness of 2.5 mm for η -MoC/Co@NC. The "Host-Guest" precursor induced the uniformly distributed η -MoC and metallic Co nanoparticles in the N-doped carbon matrix, generating abundant 3d/4d hetero-interfaces and intense synergistic interaction. The crucial role of thermal stability of the crystalline framework and phase conversion among multi-components were investigated, which lighten the structural design of the high-performance EWAMs in the future. Graphical abstract: A brilliant structural design strategy of Host-Guest structural precursor (Mo-POM@Co-ZIF) was proved for obtaining a high-efficient EWAM ( η -MoC/Co@NC). The highly porous structure and uniformly distributed hetero-interfaces enhanced the electromagnetic attenuation and impedance matching, displaying superior SRL of −176.39 and −159.07 at 1.5 and 2.0 mm, and wide EAB of 4.58 GHz (7.44–12.02 GHz) which covered the whole X-band at 2.5 mm. Image 1